Analisis Yuridis terhadap Tindak Pidana Pelanggaran Data Pribadi oleh Media Massa dalam Sistem Hukum Pidana Indonesia - Qurbani, Azka Shafa; Yuningsih, Henny (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Violations of personal data by the mass media have become increasingly frequent in the digital era. The openness of public information regulated under Law No. 14 of 2008 on Public Information Disclosure guarantees the public’s right to access information, but it also opens opportunities for misuse of personal data. When the media publishes personal information without consent or beyond the limits of public interest, such acts may constitute a criminal offense related to privacy violations and data misuse. This research aims to conduct a juridical analysis of personal data violations by mass media within the framework of Indonesia’s criminal law system, and to examine its relevance to the data protection principles in Law No. 27 of 2022 on Personal Data Protection (PDP Law). This study employs a normative juridical method using legislative and conceptual approaches and also reviews several actual cases of personal data misuse in the media sector. The findings indicate that data breaches committed by the media fall under Articles 67–70 of the PDP Law and are closely linked with Article 26 of Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law). Furthermore, media criminal liability is associated with liability by publication principle, as stipulated in Law No. 40 of 1999 on the Press. In conclusion, the enforcement of criminal law for personal data violations by the media must balance the right to public information and the right to individual privacy, ensuring that press freedom is preserved while maintaining legal and ethical protection for citizens’ personal data.